Self-powered X-Ray Sensors for Extreme Environments - Nurul Syazwina, M.; Wright, N.G; Horsfall, A.B (2017)
The ability to remotely monitor the radiation dose in environments where the radiation dose rate precludes the use of conventional technology offers a step change in capability. Through the use of wide band gap semiconductor materials, we show that it is possible to develop a self-powered system that harvests energy from the X-ray photon flux in the environment. This opens up the possibility of developing high power radioisotope micro batteries, where the dose encountered by the power conversion electronics is beyond the limitations of siliconbased systems.